Pertumbuhan Setek Kopi Robusta (Coffea canephora P.) yang Dirangsang Dengan Urin Sapi, Air Kelapa dan Atonik dengan Berbagai Taraf Kosentrasi - BRATA, I KADEK; SUTEDJA, I NYOMAN; ARIMBAWA, I WAYAN PASEK (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Cuttings Growth of Robusta Coffee (Coffea canephora P.) Which is Influenced with Urin Cow, Coconut Water and Atonic With Various Cosentration Taraf Robusta coffee (Coffea canephora P.) in general can be reproduced  generatively by seeds and vegetative with cuttings, because robusta coffee pollinates so that the development of robusta coffee is not recommended using generative methods or with seeds because it will form new populations with varying yield properties. Then the multiplication of Robusta coffee is done by cuttings. This study aims to determine the effect of the type of Growth regulator between cow urine, coconut water, and atonic and the effect of the concentration level of each type of Growth regulator on the growth of Robusta coffee cuttings. This study uses a nested design with 3 types of zat pengatur tumbuh and 4 levels of concentration as a treatment. The results showed growth regulators Cow urine, coconut water, and atonik both can increase the growth of Robusta coffee cuttings in nurseries depending on the concentration given, the best growth of cuttings in the administration of cow urine with a concentration of 20% with a total oven dry weight of 2.08 g which increases cuttings growth by 150.60% compared with no administration of growth regulators, The provision of coconut water with a concentration of 50% with a total oven dry weight reached 154 g which increased cuttings growth by 115,21% compared to without administration of growth regulators. and administration of Atonik with a concentration of 0,25% with a total oven dry weight of 141 g which increased cuttings growth by 67.86% compared with no administration of growth regulators.